THE EFFECT OF BOX JUMP TRAINING ON T-KICK SPEED IN PERSINAS ASAD TUGUMULYO STUDENTS, MUSI RAWAS REGENCY - Izza (Teaching and General Education Studies, 2025)
This study aims to determine how much the Box Jump Exercise influences the speed ​​of T Kicks of Persinas Asad Tugumulyo students. This study includes quantitative approach research with experimental and control methods with the independent variable of box jump exercise; the dependent variable is the increase in T kick speed. The subjects in this study were students of Persinas Asad Tugumulyo Musi Rawas Regency, athletes selected using random sampling techniques. The data collection method is the T-kick test. We administer the test to each group at the start of their treatment and again at the end. The treatment given to the experimental group was in the form of box jump exercises, while in the control class it was in the form of regular exercises after being given training for 14 meetings with a training frequency of 3 times a week. Based on the analysis of post-test data values ​​carried out using the SPSS difference test, the data obtained is that the Sig. (2-tailed) value = 0.000. When compared with the value = 0.05, the Sig. (2-tailed) value = 0.000 < 0.05. So Ho is rejected and Ha is accepted. Thus, the proposed Ha can be accepted as true; it can be concluded that there is an influence of Box Jump training on increasing the speed of T kicks of Persinas Asad Tugumulyo students, Musi Rawas Regency.